Modern Architecture: Reading Signs and Symbols in a Technological Environment - Ayub Muktiono (SEAN Institute, 2023)
In an era where technology continues to develop rapidly, modern architects are faced with the challenge of creating buildings that are not only aesthetically pleasing, but also able to communicate with their occupants through an effective visual language. This research aims to explore an in-depth understanding of how modern architecture interacts with the technological environment through the use of signs and symbols. This research method involves literature analysis to investigate the role of signs and symbols in modern architecture using a qualitative approach. The research results show that the use of signs and symbols in modern architecture, especially in the context of a technological environment, has a significant impact. Signs and symbols not only function as visual communication tools, but also as aesthetic elements that can increase the artistic value of a building. Through intelligent integration, symbols form a visual identity, create a sense of connection with technological advancements, and provide an immersive, holistic experience for residents. The implication is that the wise use of signs and symbols can guide architectural designers in creating buildings that not only combine aesthetics and technology, but also provide deeper meaning and value for the people who inhabit the building.